URBAN DESIGN AND SUSTAINABLE DEVELOPMENT: A CASE OF MAKOKO AREA OF LAGOS STATE, NIGERIA - Ajayi, Olumuyiwa O; Oviasogie, Faith O.; Azuh, Dominic E.; Duruji, Moses M. (European Scientific Journal, ESJ, 2014)
Today, cities in developing countries enmeshed in extreme poverty and fail to create the jobs necessary for development. The share of the population living in urban areas is rising inevitably. According to the report of the Global Urban Observatory (2003), urban poverty in developing countries is typically concentrated in slums and other informal settlements. The bulk of the urban poor in Africa as exemplified by the Nigerian situation are living in extremely deprived conditions and indecent housing with insufficient physical amenities like water supply, sanitation, sewerage, drainage, community centres, health care, nutrition, preschool and non-formal education. The UNDP Human Development Report 2004 ranks Nigeria as the 30th poorest country in the world, as it is now, according to the Global Competitive Index (GCI, 2013-2014), Nigeria is the 120th poorest country among 148 countries in the world. Currently about 65- 70% of the population lives below the poverty line, half of which probably lives on less than half a dollar per day and precarious situation (UNDP, 2004). The issue of poverty in Nigeria especially in the urban areas as exemplified by the situation in Lagos being the commercial nerve of the country has been aggravated by the present trend of rural urban migration coupled with the inability of the urban areas to create the jobs necessary for development. Currently Lagos reflects the embodiment of the contemporary decay of urban life as evident in the poor standard of living, congested apartments, degraded environment, crime, among others. It is against this background that this paper seeks to investigate the interplay between urban design and sustainable development in Makoko due to its strategic location in Lagos metropolis